Penerapan Probabilistic FSM pada AI musuh dalam game ARPG untuk gerakan AI tidak monoton - Nicolas Wiyendi; Djoni Haryadi Setiabudi; Hans Juwiantho (Jurnal Infra, 2021)
Game is really popular and becoming one of human aspects of life from child, Along with times the needs of game AI that’s not monotone has become more and more real, The problem that made a game monotone is the AI repeating its movement, with that the AI that doesn’t repeat its movement is made, this AI will make players not bored because of spam movement also motivated to play the game. Previous research has been made but with different genre and different random technic.Game will be developed with Probabilistic finite state machine methods combine with random shuffle bag. Probability will be used for showing the animation so it will make the animation that’s come out more than one, and random shuffle bag will be used for the decision making for the movement so its evenly divided and not repeated.Result of the testing shows that AI is not repeating the movement but it can repeat the pattern of the movement, Problem with repeating pattern can be solve with probability on animation that’s come out so with the same pattern movement player can see different movement.